2020
DOI: 10.1101/2020.09.22.308288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The fitness landscapes of translation

Abstract: Motivated by recent experiments on an antibiotic resistance gene, we investigate genetic interactions between synonymous mutations in the framework of exclusion models of translation. We show that the range of possible interactions is markedly different depending on whether translation efficiency is assumed to be proportional to ribosome current or ribosome speed. In the first case every mutational effect has a definite sign that is independent of genetic background, whereas in the second case the effect-sign … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For certain conditions they observed that the stationary current was increasing with increasing f , or decreasing with increasing p 1 . We have repeated these simulations and find the expected monotonic behavior throughout [17]. The results reported in [39] may have been caused by insufficient relaxation to the stationary state 1 .…”
Section: Ribosome Currentmentioning
confidence: 87%
See 1 more Smart Citation
“…For certain conditions they observed that the stationary current was increasing with increasing f , or decreasing with increasing p 1 . We have repeated these simulations and find the expected monotonic behavior throughout [17]. The results reported in [39] may have been caused by insufficient relaxation to the stationary state 1 .…”
Section: Ribosome Currentmentioning
confidence: 87%
“…If efficiency is identified with the stationary ribosome current, we prove rigorously that sign epistasis is not possible. In contrast, if efficiency is taken to be the average speed of a ribosome (equivalently, the inverse of the ribosome travel time), then plausible scenarios giving rise to sign-epistatic interactions are readily found, and fitness landscapes that are qualitatively similar to those observed experimentally in [7] can be constructed [17]. We conclude, therefore, that there are (at least) two different fitness landscapes of translation, one of which is always simple, whereas the other displays a complex structure of hierarchically organized neutral networks.…”
Section: Introductionmentioning
confidence: 99%